SYNTHESIS, CHARACTERISATION AND CARBON DIOXIDE ADSORPTION DESORPTION OF SOLVOTHERMOLYSED DOLOMITE - ENDOT, NOR AZAM (2012)
In this work, carbon dioxide adsorption-desorption characteristics were evaluated on calcined raw dolomite, unsupported solvothermolysed dolomite and supported solvothermolysed dolomite. Solvothermolysis was employed to prepare the adsorbents by using three solvents, namely; ethanol, water and polyethylene glycol (PEG). Aluminium hydroxide wasintroduced as the support andthe variable studied was ratios of Al (OH)3to dolomite. Adsorbents were calcined at 400 °C, 800°C and 1100 °C for 2 hours in air. Sample characterizationwas done using X-ray diffraction (XRD), N2 adsorption-desorption isotherms and thermogravimetric analysis (TGA). Solvothermolysis by ethanol as solvent produced the lowest average crystal size and decomposed at the lowesttemperature (650°C) with the highest weight lost at 800°C (38%) compared to other samples at the same temperature. Solvothermolysed dolomite using ethanol with 1:2 molar ratio of Al(OH)3 to dolomite (1:2 t-e Al: dolomite) resulted in lowest average crystallite size among other supported solvothermolysed ratios. Calcination at 800°C leads to decomposition of dolomite into mixed oxides. The specific surface area increases with increasing calcination temperature up to 800°C. At 1100°C, the surface area slightly decreased a sign of possible sintering. The C02 adsorption desorption studies were performed by using temperature programmed desorption (TPD) and three isothermal adsorption temperatures were used; 100 °C, 200°C and 300°C respectively. At 100 °C the adsorption capacity of C02 is the highest for all samples compared to higher adsorption temperatures. The dolomite solvothermolysed and calcined at 800°C has the highest amount of C02 adsorbed at all temperatures. At 300°C, 1:2 t-e Al: dolomite has better adsorption capacity, about twice, than raw dolomite. This study successfully discovered that solvothermolysis of dolomite using ethanol as the solvent reduced the decomposition temperature of dolomite and produced an adsorbent with better porosity and high C02 adsorption capacity.